Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil - Monteiro, Nilton Juvencio Santiago; Barbosa, Rodrigo Rendeiro; Esposito, Maria Cristina (Zootaxa, 2019)
We here report 35 Agromyzidae species and their associations with host-plants in the state of Pará. We describe the new species Ophiomyia falcifera sp. nov. and Phytomyza varronivora sp. nov. Eleven species, and the genera Phytomyza Fallén and Pseudonapomyza Hendel, are reported for the first time in Brazil.